2021
DOI: 10.1101/2021.02.10.21251507
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Responsive caregiving, opportunities for early learning, and children’s safety and security during COVID-19: A rapid review

Abstract: During the COVID-19 pandemic, there have been drastic changes in family life and programs and services that promote and protect early childhood development. Global stakeholders have raised concerns that the pandemic is putting enormous strain on parents and other caregivers, compromising capabilities and enabling environments for nurturing care of young children and therefore likely impacting children's development. This rapid review takes stock of emerging research on nurturing care for young children during … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 103 publications
1
18
0
Order By: Relevance
“…31 Other concerns include extensive screen time and a lack of outdoor play. 32 A Canadian study of 2,100 youth-parent pairs found that students reported changed behaviours associated with school closures. 33 Most youth were found to be spending less time on homework, sleeping more than before, and almost half find school less interesting than before COVID-19.…”
Section: Impact Of School Closures On Overall Well-beingmentioning
confidence: 99%
“…31 Other concerns include extensive screen time and a lack of outdoor play. 32 A Canadian study of 2,100 youth-parent pairs found that students reported changed behaviours associated with school closures. 33 Most youth were found to be spending less time on homework, sleeping more than before, and almost half find school less interesting than before COVID-19.…”
Section: Impact Of School Closures On Overall Well-beingmentioning
confidence: 99%
“…Moreover, researchers have been stressing that this decrease should not be attributed to an increase in the safety of children but rather due to the adverse impact of the lockdown on the system's ability to see and protect children (e.g., Baron et al, 2020;Katz & Cohen, 2020). In addition, there is growing evidence that during COVID-19, various CM risk factors significantly increased (Conrad-Hiebner & Byram, 2020;Proulx et al, 2021;Rodriguez et al, 2020;Wu & Xu, 2020), such as parental job loss (Lawson et al, 2020), parental social isolation (Lee et al, 2021), and mental health issues (Russell et al, 2020). Adding to this, parental stress was found to be a major CM risk factor that increased during COVID-19 and an increase in selfreported child abuse was found for parents experiencing heightened stressors (Lawson et al, 2020).…”
mentioning
confidence: 99%
“…Put simply, it makes a difference if a parent tends to be controlling due to specific values or stress exposure and thus, gets involved in homework, in a controlling way, some days a week for up to an hour, or if she/he gets involved, in a controlling way, 5 days a week for several hours. Moreover, a recent research review indicates that lockdowns lead to more parental stress and stress outcomes (e.g., depression, burnout), especially in low SES families and in parents of younger children, which was also accompanied by harsher and less warm parenting (Proulx et al, 2021). Thus, lockdowns might especially increase stress exposure of low SES parents, which in turn affects their involvement in distance learning.…”
Section: The Current Studymentioning
confidence: 99%